2019
DOI: 10.1088/1742-6596/1425/1/012094
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of the coefficient of thermal expansion of building materials based on polyvinyl chloride

Abstract: The possibility of predicting the coefficient of thermal expansion for the blends of polyvinyl chloride (PVC) with a number of organic polymers is shown. It was found that the higher the glass transition temperature of the polymer, the lower the coefficient of thermal expansion of the mixture of PVC with this polymer. The dependence of thermal expansion for composites based on wood of different species and bamboo is also analyzed. In all cases, the coefficient of thermal expansion is reduced, which allows the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…high temperature. Ti6Al4V shows indeed a specific heat of Sensitivity Dimensions [22] 5 fF/g 0.4 x 0.6 x 0.1 mm 3 [23] 8.7 pF/g 4 x 4 x 0.59 mm 3 [12] 33.16 fF/g 30.4 x 9 x 2 mm 3 [12] 31.44 fF/g 22.4 x 9 x 2 mm 3 [this work] 184 fF/g 28 x 23 x 15 mm 3 553J/Kg K, a thermal conductivity of 6.6-6.8W/m K and a thermal expansion coefficient of 8.6•10 -6 K -1 [24], that guarantee a much better thermal behavior than polymer based sensors, whose thermal expansion coefficients are usually at least one order of magnitude bigger [33]- [34] and that can only operate far below the glass-transition temperature [35]. A different consideration must be done if we want to compare metal sensors as the one here proposed, with polymer based sensors metallized through a Cu layer [12]- [14].…”
Section: Discussionmentioning
confidence: 99%
“…high temperature. Ti6Al4V shows indeed a specific heat of Sensitivity Dimensions [22] 5 fF/g 0.4 x 0.6 x 0.1 mm 3 [23] 8.7 pF/g 4 x 4 x 0.59 mm 3 [12] 33.16 fF/g 30.4 x 9 x 2 mm 3 [12] 31.44 fF/g 22.4 x 9 x 2 mm 3 [this work] 184 fF/g 28 x 23 x 15 mm 3 553J/Kg K, a thermal conductivity of 6.6-6.8W/m K and a thermal expansion coefficient of 8.6•10 -6 K -1 [24], that guarantee a much better thermal behavior than polymer based sensors, whose thermal expansion coefficients are usually at least one order of magnitude bigger [33]- [34] and that can only operate far below the glass-transition temperature [35]. A different consideration must be done if we want to compare metal sensors as the one here proposed, with polymer based sensors metallized through a Cu layer [12]- [14].…”
Section: Discussionmentioning
confidence: 99%
“…6b, at representative temperatures of the material, alpha 1 represents the CLTE at temperatures below Tg and alpha 2 represents the coefficient of thermal expansion for temperatures above Tg. It was found that the coefficient of thermal expansion CLTE decreases 70% under the Tg, for the PC sterilized by dry heat, After Tg, the CLTE of the PC with the two sterilization processes are practically the same, the change in the slope of the curves Expansion below and above Tg is related to the expansion of the free volume [44]. The coefficients of thermal expansion found differ from those presented according to [45] for PC (110-130 μm / (m • ° C)), this difference can be attributed to the fact that 3D printing has free space in its structure despite of a 100% print fill density.…”
Section: Resultsmentioning
confidence: 96%
“…However, due to their high coefficient of thermal expansion, plastics tend to change their dimensions significantly, which is a problem that must be considered for certain applications [61]. Furthermore, they are poor thermal conductors in general.…”
Section: Thermal Propertiesmentioning
confidence: 99%